Kontroversi Kurikulum Merdeka: Tantangan dan Potensi Transformasi Pendidikan Islam - Arini Nuora Darina; Misbahul Arifin; Tiara Nurul Annisa' (Educational Research Center, 2025)
This study examines the dynamics of implementing the Merdeka Curriculum in Islamic educational settings through a case study at MI Al-Hanafiyah Talkandang, Paiton, Probolinggo. The main focus is to uncover the tension between deeply rooted Islamic traditions and the demands of national curriculum innovation, while exploring evidence-based approaches to bridge the gap. Using a qualitative method with a case study design, data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings reveal that despite initial resistance, the school developed adaptive strategies through theme modification, integration of Islamic values, and stakeholder involvement. These results highlight the importance of a reflective-contextual approach in responding to national policy, and demonstrate that educational transformation in Islamic contexts can emerge from strong local foundations. The study contributes a contextual and practical model for curriculum adaptation in madrasahs